PERLINDUNGAN HUKUM BAGI PEMODAL DALAM PENYELENGGARAAN LAYANAN URUN DANA BERBASIS TEKNOLOGI INFORMASI (SECURITIES CROWDFUNDING) - Silvia Arleinia (2022)
The research in this final project discusses legal protection for investors in securities crowdfunding (SCF) services in Indonesia. The primary focus of this research is what kind of form of the legal relationship between the parties based on POJK Number 57/POJK.04/2020 and what kind of legal protection provided by OJK to users, especially for investors in SCF. The aim of this research is to know and understand how the form of legal protection provided to investors in crowdfunding services based on existing regulations and to examine the form of legal relations between the parties. The research method used in this final project is a normative juridical research method with a statute approach. Based on the results of the research conducted, it can be ascertained that the parties in implementing SCF are interconnected with each other. Afterward preventive and repressive legal protection for SCF users, especially investors, are contained in Law Number 8 of 1995 of Capital Markets, Law No. 21 of 2011 on Financial Services Authority, POJK Number 1/POJK.07/2013 on Consumer Protection in the Financial Services Sector and POJK Number 57/POJK.04/2020 on Securities Offering Through Crowdfunding Services Based on Information Technology.